Political Consciousness in the Select Works of Chinua Achebe, Ngugi Wa Thiong’o and Richard Wright - Gautam, Shreedhar (The Harvest, 2023)
This paper introduces three writers Chinua Achebe, Ngugi Wa Thiong’o and Richard Wright to explore the socio political consciousness reflected in their select works. The first two writers come from African countries which have gone through the experience of colonialism and neo-colonialism that resulted in common social, political and economic problems. As a result, the literature that emerged from these countries has a unifying theme despite diverse sociological contexts. Richard Wright, with an African origin, is a prominent black writer from America. It is evident from wright’s writings that he writes with a political consciousness born out of his understanding of Marxism. These three writer of twentieth century display their creative talents to raise the consciousness of the suppressed people in their own countries and the world over. An effective presentation of the contemporary social as well as political problem has become the primary task of these writers, and the select works taken here serve as evidences.